Comparative Analysis of the Financial Performance of PT Gudang Garam and Sampoerna 2021–2024 - Rahma Satya Masna Hatuwe; Andity Rahman Wally (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze and compare the financial performance of two leading cigarette companies in Indonesia, PT Gudang Garam Tbk (GGRM) and PT Hanjaya Mandala Sampoerna Tbk (HMSP), during the 2021–2024 period. The analysis was conducted using financial ratios, including liquidity, solvency, activity, and profitability ratios, with data sourced from each company's annual financial reports published on the Indonesia Stock Exchange. The research method used was a comparative quantitative approach with total sampling because the study population only included these two companies. Data were processed using the Current Ratio, Quick Ratio, Cash Ratio, Debt to Equity Ratio, Debt to Asset Ratio, Total Asset Turnover, Receivable Turnover, Return on Assets, Return on Equity, and Net Profit Margin. The results indicate that both companies experienced performance pressures during the study period, primarily due to rising excise rates, production cost inflation, changing consumer preferences, and increasingly stringent government regulations. However, HMSP generally demonstrated better financial performance stability than GGRM, particularly in terms of liquidity and profitability. GGRM tends to be more volatile and sensitive to external changes, as evidenced by significant declines in net profit and profitability ratios in certain years.